The Effect of Communication Media on Information Sharing in Supply Chains - Lennart C. Johnsen; Guido Voigt; Joachim Weimann (Production and Operations Management, 2019)
Using laboratory experiments, we study how communication media affect cooperation in a supply chain when the buyer has private information about the end-customer demand. We show that coordinating contracts (quantity discount) combined with efficient means to electronically share private information (one-way, pre-defined text message) result in almost efficient outcomes, but only if verbal communication takes place before the actual contracting stage. Content analysis shows that verbal communication is especially effective in establishing trust and trustworthiness when players talk about reciprocal strategies and it is more so when the buyer clearly expresses guilt from lying. Furthermore, the clarification of the mutual benefits of information sharing moves the buyer to truthfulness. Finally, we show that our results are not due to a reputation building mechanism of repeated interaction.
Keywords: 650; asymmetric information; cheap talk; trust; trustworthiness; behavioral operations management